Form of Performance and Creativity of the Sisingaan Art in Wanareja Group in Subang Regency, West Java - Witriani, Rani; Sumaryanto. F, Totok; Malarsih, Malarsih (Universitas Negeri Semarang, 2019)
Sisingaan Art is an art which is still developing in Subang Regency, West Java. Sisingaan Art of the Wanareja group is one of the groups from Subang Regency which has developed Sisingaan art with Demon creativity (demonstration) since 1987. This study aims to analyze the form of performance and creativity of the Sisingaan art in the Wanareja group in Subang Regency, West Java. The method used in this study is qualitative method with an interdisciplinary approach. Data collection techniques used are observation, interview, and document study. The data are validated by using the triangulation technique and interactive data analysis technique. Based on the results of the research, in the form of performance and creativity of Sisingaan art, there found a Demon style (demonstration) carried out at the end of the procession. Demon style (demonstration) is in the form of attractions, namely Demon of gugunungan, kakapalan, renengan punggu and kidung. Therefore, the Sisingaan art of the Wanareja group is very attractive to audiences from any class of society. The implication of the Sisingaan art of the Wanareja group is to maintain and develop Sisingaan art in the Wanareja group through forms of performance and creativity. For the society, it functions for entertainment and preserving Sisingaan art.